2020
DOI: 10.3892/ol.2020.11670
|View full text |Cite
|
Sign up to set email alerts
|

CD73 promotes colitis‑associated tumorigenesis in mice

Abstract: Patients with inflammatory bowel disease (IBD) are at a higher risk of developing colitis-associated colorectal cancer. The aim of the present study was to investigate the role of CD73 in IBD-associated tumorigenesis. A mouse model of colitis-associated tumorigenesis (CAT) induced by azoxymethane and dextran sulfate sodium was successfully constructed. Model mice were injected with CD73 inhibitor or adenosine receptor agonist. Colon length, body weight loss and tumor formation were assessed macroscopically. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
0
12
1
Order By: Relevance
“…These findings suggest that transplantation of CD73 + cells could lead to tumor formation. However, the promotion of colitis-associated tumorigenesis by CD73 reported by Liu et al was observed in a chronic inflammatory model generated following three cycles of treatment with azoxymethane, a genotoxic colonic carcinogen, and DSS administration for 3 weeks (Liu et al, 2020), which is different from the acute colitis model used in the present study. Moreover, transplanted MSCs disappear after temporary engraftment (Kean et al, 2013), but we will further investigate whether CD73 + cell spheroids remain at the injured site for a long time using longitudinal analysis, considering the potential clinical application of MSC transplantation.…”
Section: Secretory Factors Of Cd73 + Cell Spheroids Induce Alteration...contrasting
confidence: 70%
See 1 more Smart Citation
“…These findings suggest that transplantation of CD73 + cells could lead to tumor formation. However, the promotion of colitis-associated tumorigenesis by CD73 reported by Liu et al was observed in a chronic inflammatory model generated following three cycles of treatment with azoxymethane, a genotoxic colonic carcinogen, and DSS administration for 3 weeks (Liu et al, 2020), which is different from the acute colitis model used in the present study. Moreover, transplanted MSCs disappear after temporary engraftment (Kean et al, 2013), but we will further investigate whether CD73 + cell spheroids remain at the injured site for a long time using longitudinal analysis, considering the potential clinical application of MSC transplantation.…”
Section: Secretory Factors Of Cd73 + Cell Spheroids Induce Alteration...contrasting
confidence: 70%
“…Inhibition of CD73 activity or gene silencing in tumor cells is reported to attenuate tumorigenesis (Jin et al , 2010; Stagg et al , 2010). Additionally, CD73 is highly expressed in solid tumors and is reported to facilitate colitis-associated tumorigenesis (Liu et al , 2020; Roh et al , 2020). These findings suggest that transplantation of CD73 + cells could lead to tumor formation.…”
Section: Discussionmentioning
confidence: 99%
“…Considering elevated purinergic signaling levels in colon cancer samples, we strongly suppose that purinergic ecto-enzymes can be responsible for a similar antiinflammatory/immunosuppressive role in colorectal tumorigenesis (X.-H. Liu et al 2020). Given their immunosuppressive powers, it would not be surprising to see that these proteins are highly expressed in the colorectal tumor microenvironment (Liu et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…While some studies associate stromal CD73 expression with higher tumorigenic potential in colorectal cancer (Wu et In CRC studies with the cell lines, tumor cell specific CD73 expression was found to be essential for tumor growth in vitro and in vivo (Wu et al 2016). However, in a colitis associated cancer model, use of CD73 specific inhibitor reduced the tumor burden (Liu et al 2020). On the contrary, another report suggested that tumor cell specific CD73 expression is dispensable for colorectal tumor growth while stroma specific (mesenchymal cells) CD73 expression was essential for CD73-driven tumor growth (Yu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, concentrations of N-acetylaspartate produced by ovarian cancer cells were found to increase in parallel with cancer progression and correlated with, the polarization of macrophages towards the M2-like phenotype [156]. Non-specific stimulation of ARs by the agonist NECA upregulated the expression of NAT8L RNA in a colitis-associated tumorigenesis mouse model [157]. Because CD73 inhibitor conversely downregulated NAT8L expression, the observations were ascribed to AR modulation.…”
Section: Prospective Targets Of Adenosinergic Therapymentioning
confidence: 96%